Over-expression in Escherichia coli and characterization of two recombinant isoforms of human FAD synthetase. - Brizio, C; Galluccio, M; Wait, R; Torchetti, E; Bafunno, V; Accardi, R; Gianazza, E; Indiveri, C; Barile, M (2006)
FAD synthetase (FADS) (EC 2.7.7.2) is a key enzyme in the metabolic pathway that converts riboflavin into the redox cofactor FAD. Two hypothetical human FADSs, which are the products of FLAD1 gene, were over-expressed in Escherichia coli and identified by ESI-MS/MS. Isoform 1 was over-expressed as a T7-tagged protein which had a molecular mass of 63kDa on SDS-PAGE. Isoform 2 was over-expressed as a 6-His-tagged fusion protein, carrying an extra 84 amino acids at the N-terminal with an apparent molecular mass of 60kDa on SDS-PAGE. It was purified near to homogeneity from the soluble cell fraction by one-step affinity chromatography. Both isoforms possessed FADS activity and had a strict requirement for MgCl(2), as demonstrated using both spectrophotometric and chromatographic methods. The purified recombinant isoform 2 showed a specific activity of 6.8+/-1.3nmol of FAD synthesized/min/mg protein and exhibited a K(M) value for FMN of 1.5+/-0.3microM. This is the first report on characterization of human FADS, and the first cloning and over-expression of FADS from an organism higher than yeast.